Automated Data Integration of Biodiversity with OLAP and OLTP - Arie Vatresia; Asahar Johar; Ferzha Putra Utama; Sinta Iryani (SISFORMA, 2020)
Biodiversity is one of emerging issue over decades; many have performed research to map and to document the data over the world. This issue is very important due to the event of extinction have been accelerating happening because of human extinction. Bengkulu, as one of the province lied in one of 19 hotspots in the world, Sundanese, has experienced the degradation of flora and fauna over the case of forest degradation and habitat loss. Although many application and software has been developed to solve the case, the existences of data standardization still become an issue over this problem. In this research, study of data integration had been developed to make the process of biodiversity data acquisition can be more effective and efficient. The system proposed the integration based on OLAP and OLTP that will be connected to IUCN, as one of the biggest center for monitoring the loss of biodiversity all around the world. This application had been built with web based using UML design and followed SDLC to provide the best fit of the need. This research had also succeeded to build the automated integration to show the record of dynamic number over biodiversity existences in Bengkulu. The application had been tested using black box and has the perfect performance (100%) over the testing that can help the monitoring process over biodiversity data.